Efficient pathogen screening in honey bees: Application of FTA® cards for DNA storage and PCR analysis - Kristýna Myslínová; Silvie Dostálková; Jana Jemelková; Beata Hurychová; Ondřej Biemann; Jan Brus; Jana Fürstová; Marek Petřivalský; Jiří Danihlík (PLoS ONE, 2025)
Screening honey bee pathogens is crucial for early infection detection, which helps prevent pathogen transmission. The most widely used method for pathogen detection in honey bees is polymerase chain reaction (PCR). FTA ® cards (Qiagen) were compared with DNA-isolation kit DNeasy Plant Mini kit (Qiagen) for the detection of selected pathogens in honey bee samples collected from colonies in the Czech Republic in autumn and spring. FTA ® cards provide highly accurate results for detecting N. ceranae with a sensitivity of 97.2% and a specificity of 100%. Thus, FTA ® cards represent a reliable and cost-effective alternative to traditional methods for N. ceranae detection. Seasonal variation in pathogen prevalence was also assessed using FTA ® cards, revealing significant differences between autumn and spring. In total 85 samples were analysed for main bee pathogens ( N. ceranae , Nosema apis , Lotmaria passim , Crithidia mellificae, and Serratia marcescens ). Greater diversity pathogen occurence was observed in autumn, with 32% of colonies showing no detectable levels of the tested pathogens, 48% infected by one pathogen, 16% by two, and 4% by three; whereas in spring, 40% of colonies tested negative for all target pathogens, with 51% infected by one pathogen and 9% by two. In autumn 2020, S. marcescens was the most prevalent pathogen (46%), followed by N. ceranae (28%) and L. passim (18%), while no C. mellificae or N. apis were detected. In spring 2021, N. ceranae dominated with a 60% prevalence, and other pathogens were detected in only one sample each. FTA ® were found to be a more economical and faster alternative to commercial DNA isolation kits, particularly for N. ceranae . Moreover, FTA® cards maintained DNA stability under challenging conditions, including high temperatures, UV radiation, and oxidative stress, making them highly suitable for field applications. Collecting field samples on FTA ® cards preserves DNA integrity and mitigates degradation risks associated with improper shipment of whole bees.